EFEKTIVITAS PROGRAM KARTU PRAKERJA ERA PANDEMI COVID-19 DI DINAS TENAGA KERJA DAN TRANSMIGASI DAERAH PROVINSI SULAWESI UTARA - Memah, Natasya Imanuela; Rares, Joyce J.; Waleleng, Grace J. (AGRI-SOSIOEKONOMI, 2022)
This study aims to determine the effectiveness of the pre-employment card program in the era of the COVID-19 pandemic at the Department of Manpower and Transmigration of North Sulawesi Province. This research was conducted from October to December 2021. This research used a descriptive qualitative method. The results showed that the achievement of the goals of the pre-employment card program in North Sulawesi was in great demand by the community as evidenced by the interest of the participants. The pre-employment card program can overcome employment problems in Indonesia as evidenced by the decline in the unemployment rate based on BPS data in 2021. Integration, the pre-employment card program needs to be socialized in more detail, not just disseminating information on pre-employment registration but including technical steps to minimize obstacles that will be experienced by pre-employment card participants. The adaptation of the pre-employment card program has adapted to technological developments, with this program the community has more control over the use of digitization which is the need of every human being at this time. So it can be concluded that the pre-employment card program in North Sulawesi in terms of indicators of achieving goals, integration and adaptation shows that its implementation is quite effective in the era of the COVID-19 pandemic.